Influence of feed gas composition on structural transformation and guest exchange behaviors in sH hydrate – Flue gas replacement for energy recovery and CO2 sequestration. (15th September 2020) - Choi, Wonjung; Lee, Yohan; Mok, Junghoon; Seo, Yongwon
Abstract: This study investigated the influence of feed gas composition on structural transformation and guest exchange behaviors in the replacement of sH (CH4  + methylcyclopentane) hydrate with CO2  + N2 for energy recovery and CO2 sequestration. CO2  + N2 mixtures with three different CO2 concentrations (20, 40, and 60%) were used as replacement gases, and their exchange behaviors were observed with gas chromatography, nuclear magnetic resonance, and powder X-ray diffraction. The experimental results demonstrated that an increase in the CO2 concentration of replacement gases increased the structural transformation of sH to sI, which resulted in the enhancement of both the extent of replacement and the guest exchange rate. However, the highest extent of replacement was observed in the CO2 (40%) and N2 (60%) mixture due to the asymmetrical change in the CO2 and N2 compositions in the replaced hydrates, which was caused by the higher degree of structural transformation in feed gas with a higher CO2 concentration and the larger N2 inclusion in replaced hydrates at the lower CO2 concentration. The experimental results obtained in this study are helpful for accurately understanding the replacement mechanism and guest exchange behaviors in sH hydrate–flue gas replacement. Graphical abstract: Image 1 Highlights: The influence of feed gas on sH hydrate–flue gas replacement was investigated. The highest extent of replacement was observed for the CO2 (40%) + N2 (60%) mixture. The higher CO2 concentration induced a higher degree of structural transformation. Structural transformation affected both replacement efficiency and production rate. The extent of replacement was affected by structural transformation and N2 inclusion.